Comparing coronavirus (COVID-19) and climate change perceptions: Implications for support for individual and collective-level policies - Poortinga, Wouter; Latter, Briony; Wang, Susie (Frontiers in Psychology, 2022)
COVID-19 (coronavirus) and climate change are both global issues that have wide-reaching and serious consequences for human health, the economy, and social outcomes for populations around the world, and both require a combination of systemic governmental policies and community support for action. This paper compares people’s responses to the coronavirus pandemic and climate change in the UK. A representative survey of the UK population (n=1,518) conducted in November and December 2020 explored public perceptions of (a) personal and government responsibility, (b) efficacy and trust, and (c) support for policies to address the two issues. The results show that, while there are a number of similarities between coronavirus and climate change, major differences exist regarding individual action. In comparison to the coronavirus pandemic, people feel less personal responsibility, think that their own personal actions are less efficacious, and express lower levels of support for (in particular individual-level) policies to address climate change. These findings suggest that experiences from the coronavirus pandemic cannot directly be translated to climate change, and thus that climate change is likely to require different policy responses and framing.